Using Virtual Reality to Help Teachers Improve Learning: A Review - Indriati, Gustina (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
Virtual reality (VR) is no longer a new concept in today's digital world. This technology has developed quite rapidly and can now be applied in many fields. The first and most important aspect of everyday life is education. In this article, researchers review current research and previous research to understand the specifics of the use of virtual reality (VR) technology as a substitute for traditional learning media. The A Review (SLR) method was used. utilizes defining the research question as the primary methodology. Search procedures were carried out using Scopus data as the basis and tool. Publish or Perish 8 and article creation are based on inclusive and exclusive criteria. that relate to the research questions above. The findings are in the form of a study of several aspects regarding the use of virtual reality as an educational medium, such as types. The technology used, the location of educational institutions using virtual reality, the domain of education, teacher preparation, virtual reality educational techniques, and the purpose and benefits of its use.